Hydrated deep eutectic electrolyte for all-weather zinc-based battery and application of hydrated deep eutectic electrolyte
By developing a hydrated deep eutectic electrolyte in a wide climate domain, using hydrogen bond coordination small molecules to regulate the behavior of complex water molecules, the stability and side reaction problems of aqueous zinc ion batteries in low temperature or high temperature environments are solved, and efficient charging and discharge and long life in a wide temperature range are achieved, and the preparation method is safe and low-cost.
Patent Information
- Application Number
- CN202411856338.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Water-based zinc ion batteries have stability and side reaction problems in low-temperature or high-temperature environments. The existing improved methods have toxicity and high cost, which violates the safety and low-cost characteristics of water-based zinc batteries.
A hydrated deep eutectic electrolyte with a wide temperature domain in a climate is developed. The hydrogen bond coordination small molecules regulate the behavior of complex water molecules, participate in the solvation of Zn2+, and inhibit hydrogen evolution and corrosion side reactions.
It achieves stable charge and discharge and cycling performance within the temperature range of -20℃~50℃, extends the service life of the battery, solves the problems of zinc negative electrode side reaction and dendrites at high and low temperatures, and is simple in preparation, low in cost, safe and environmentally friendly.
Smart Images

Figure HDA0005191907030000011 
Figure HDA0005191907030000012 
Figure HDA0005191907030000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery electrolytes, and in particular to a hydrated deep eutectic electrolyte and applications thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life and low self-discharge rate. They are the mainstream secondary batteries in today's society and play an important role in electronic equipment, energy and other fields. However, lithium-ion batteries have disadvantages such as high manufacturing cost and low safety. The emerging aqueous zinc-ion batteries have the characteristics of high energy density, low cost, safety and environmental protection, and have attracted the attention of many researchers.
[0003] However, since the electrolyte of aqueous zinc-ion batteries contains a large amount of water, a series of problems arise. Such as positive electrode dissolution, negative electrode corrosion, passivation, and hydrogen evolution reaction. The electrolyte, as the "blood" of the battery, plays an irreplaceable role in the efficient circulation of the battery. To solve the above problems, the reported work mainly improves them by designing high-concentration electrolytes, ionic liquids, hydrogels and other strategies. However, these methods are toxic and costly, which completely deviates from the advantages of aqueous zinc batteries, which are safe and low-cost.
[0004] Deep eutectic solvents (DESs), as a eutectic system solvent composed of hydrogen bond donors (HBD) and hydrogen bond acceptors (HBA), have attracted widespread attention in recent years due to their environmental friendliness and sustainability of bio-sources. Therefore, in order to promote the application of aqueous zinc-ion batteries in the field of large-scale energy storage, it is particularly important to further develop a safe, environmentally friendly zinc-based eutectic electrolyte with a wide temperature adaptability range. Summary of the invention
[0005] In order to solve the bottleneck problem of aqueous zinc batteries in low-temperature or high-temperature environments mentioned above, the primary purpose of the present invention is to provide a low-cost, simple-to-proportion hydrated deep eutectic electrolyte that can stably operate in a wide temperature range from low temperature to high temperature.
[0006] Another object of the present invention is to provide an application of the above-mentioned hydrated deep eutectic electrolyte. The hydrated deep eutectic electrolyte can be used for the preparation of aqueous zinc batteries and can be effectively applied to various harsh environment scenarios.
[0007] Another object of the present invention is to provide an all-weather aqueous zinc-based battery. The all-weather aqueous zinc-based battery can operate stably and reversibly in a temperature range of -20 to 50°C.
[0008] The purpose of the present invention is achieved through the following solutions:
[0009] A hydrated deep eutectic electrolyte for an all-weather zinc-based battery, characterized in that the electrolyte consists of a zinc salt, a hydrogen-bonding ligand and an additional water solvent.
[0010] Furthermore, the volume ratio of the water solvent to the hydrogen bonding ligand is 1:1-5, and the concentration of the zinc salt aqueous solution in the electrolyte is maintained at 2 mol·L-1.
[0011] Furthermore, the zinc salt includes at least one of Zn(ClO4)2·6H2O, Zn(BF4)2·6H2O and ZnSO4·7H2O.
[0012] Furthermore, the hydrogen bonding ligand includes at least one of acetylacetone, acetylacetone and acetylacetic acid.
[0013] Secondly, the present application also includes an all-weather zinc-based battery hydrated deep eutectic electrolyte for the preparation of an all-weather zinc-based battery.
[0014] In addition, the present application also includes an all-climate aqueous zinc-based battery, characterized in that it includes a positive electrode, a negative electrode and an all-climate zinc-based battery hydrated deep eutectic electrolyte, and the preparation method of the positive electrode is to load at least one of a conductive polymer and a vanadium-based compound on a substrate.
[0015] Furthermore, the conductive polymer is at least one of polyaniline and polypyrrole; the vanadium-based compound is at least one of vanadium dioxide, vanadium pentoxide, sodium vanadate, basic zinc vanadate, sodium vanadium phosphate and sodium vanadium parafluorophosphate; the substrate is commercial carbon paper and titanium foil roughened by acid etching; the loading amount of at least one of the conductive polymer and the vanadium-based compound on the substrate is 2 to 20 mg cm -2 The electrode thickness is between 0.15 and 1.5 mm, and the tap density is between 0.6 and 3.5 g / cm 3 .
[0016] Furthermore, the loading method includes in-situ polymerization, blade coating or hydrothermal synthesis; the negative electrode is a high-purity zinc metal foil with a thickness of 10 to 100 μm, or is obtained by anodic deposition of zinc film or brushing of zinc slurry on titanium foil, stainless steel foil, or carbon paper, and the thickness is controlled at 5 to 30 μm.
[0017] Finally, the present application also includes a method for preparing an all-weather aqueous zinc-based battery, which is characterized in that it includes the following steps: assembling the positive electrode, hydrated deep eutectic electrolyte and negative electrode into an aqueous zinc-ion battery with different device structures.
[0018] Furthermore, the method specifically uses glass fiber as a separator. If a standard button shell is used to encapsulate a button battery at a pressure of 70-90 MPa, the amount of hydrated deep eutectic electrolyte added is 50-100 μL.
[0019] The mechanism of the present invention is to regulate the behavior of complexed water molecules through hydrogen bond coordination of small molecules, thereby participating in the Zn 2+The solvation behavior of Zn 2+ Efficient and stable deposition. In addition, by means of hydrogen bond coordination of small molecular polar oxygen-rich functional groups and anions or water molecules in hydrated zinc salts, strong hydrogen bond interactions are formed, the behavior of active free water molecules is regulated to inhibit the occurrence of hydrogen evolution side reactions, and at the same time, the corrosion side reactions are greatly reduced by adsorbing on the surface of zinc negative electrode with maximum binding energy. It is worth noting that as the main component of the electrolyte, hydrogen bond coordination small molecules control the content of active water molecules from the source, and greatly reduce the mutual hydrogen bonding between active water molecules, effectively inhibiting the tetrahedral water molecule structure required for ice formation. Among them, since organic coordination small molecules are widely involved in the structural formation of eutectic electrolyte system under room temperature environment, the solvation structure type and distribution uniformity of zinc ions are significantly increased, and the sudden change of electrolyte structure under high temperature environment and the accelerated evaporation of active water molecules are effectively stabilized. Finally, by further regulating the content of the introduced additional water molecules, the transport kinetic properties such as ionic conductivity of the hydrated deep eutectic electrolyte system can be optimized to solve the bottleneck of insufficient ion transport capacity at low temperature and poor stability in high temperature environment.
[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0021] The all-weather zinc-based hydrated deep eutectic electrolyte provided by the present invention, zinc salts and hydrogen-bonding ligands are mixed to form a eutectic solvent, which is in a liquid state at room temperature. Through the action of hydrogen bonds, the solubility of zinc salts and hydrogen-bonding ligands is improved, thereby improving the conductivity of the battery and the stability of the electrolyte. Importantly, the electrolyte of the present invention exhibits a high charge and discharge capacity and excellent cycle stability under all-weather conditions (-20°C to 50°C), effectively expands the operating temperature range of aqueous zinc-ion batteries, solves the problems of zinc negative electrode side reactions and dendrite growth under high and low temperatures, greatly prolongs the service life of aqueous zinc-ion batteries, and is of great significance in the field of energy storage. In addition, the preparation method of the all-weather zinc-based hydrated deep eutectic electrolyte provided by the present invention is simple, rapid, low-cost, safe, green and pollution-free, and suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Long cycle diagram of Zn-Zn battery assembled with the electrolytes in Example 1 and Comparative Example 1 at 25°C;
[0023] Figure 2 The charge-discharge cycle performance diagram of the Zn-Zn battery assembled with the electrolytes in Example 2 and Comparative Example 2 at 50°C;
[0024] Figure 3 The cycle performance diagram of the Zn-Zn battery assembled with the electrolyte in Example 3 and Comparative Example 3 at -20°C;
[0025] Figure 4 XRD test diagram of Zn-Zn battery assembled with the electrolyte in Example 4 and Comparative Example 4 at 25°C;
[0026] Figure 5 The SEM test images of the Zn-Zn batteries of Example 5 and Comparative Example 5 at 25°C;
[0027] Figure 6 This is a long cycle performance diagram of the Zn||VOX battery of Example 6 and Comparative Example 6 at 25°C. DETAILED DESCRIPTION
[0028] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below with reference to the accompanying drawings. However, the present invention can be implemented in many other ways different from those described herein, so the present invention is not limited to the specific implementation disclosed below.
[0029] Example 1
[0030] A hydrated deep eutectic electrolyte for all-weather zinc-based batteries, levulinic acid and deionized water are mixed at a volume ratio of 1:1 and stirred at room temperature as a solvent, then zinc sulfate is added as a solute to control its concentration to 2 mol / L, and stirred at room temperature for 60 minutes to obtain a clear and transparent electrolyte named DES50. The above hydrated deep eutectic electrolyte is used to verify the effect of levulinic acid on inducing uniform deposition of zinc ions.
[0031] Using zinc foil as positive and negative electrodes and glass fiber as separator, 120 μL of the above electrolyte was taken to assemble a CR2032 button-type symmetrical battery, and the cyclic charge and discharge test was carried out on the Xinwei battery test system. The test temperature was 25°C and the current density was 5 mA cm -2 , with a surface capacity of 1 mAh cm -2 .
[0032] Comparative Example 1
[0033] At room temperature, 14.378 g of zinc sulfate heptahydrate was added to 25 ml of deionized water and ultrasonicated for 20 min to completely disperse it, and 25 ml of an electrolyte containing 2 mol / L zinc sulfate was prepared, named DES0.
[0034] Using zinc foil as positive and negative electrodes and glass fiber as separator, 120 μL of the above electrolyte was taken to assemble a CR2032 button-type symmetrical battery, and the cyclic charge and discharge test was carried out on the Xinwei battery test system. The test temperature was 25°C and the current density was 5 mA cm -2 , with a surface capacity of 1 mAh cm -2 .
[0035] The test results are as follows Figure 1As shown, the symmetrical battery assembled using Comparative Example 1 has a reduced cycle life due to side reactions such as zinc dendrites and hydrogen evolution corrosion during the cycle. In contrast, Example 1 assembled using the zinc-based hydrated deep eutectic electrolyte prepared by the present invention greatly extends the number of cycles of the battery. Specifically, DES50 can cycle for about 1800 hours. At the same time, adding a certain volume fraction of levulinic acid reduces the polarization voltage of the hydrated deep eutectic electrolyte.
[0036] Example 2
[0037] A hydrated deep eutectic electrolyte for all-weather zinc-based batteries, levulinic acid and deionized water are mixed at a volume ratio of 1:1 and stirred at room temperature as a solvent, then zinc sulfate is added as a solute to control its concentration to 2 mol / L, and stirred at room temperature for 60 minutes to obtain a clear and transparent electrolyte named DES50. The above hydrated deep eutectic electrolyte is used to verify the effect of levulinic acid on inducing uniform deposition of zinc ions.
[0038] Using zinc foil as positive and negative electrodes and glass fiber as separator, 120 μL of the above electrolyte was taken to assemble a CR2032 button-type symmetrical battery, and the cyclic charge and discharge test was carried out on the Xinwei battery test system. The test temperature was 50°C and the current density was 0.25 mA cm -2 , the surface capacity is 0.25 mAh cm -2 .
[0039] Comparative Example 2
[0040] At room temperature, 14.378 g of zinc sulfate heptahydrate was added to 25 ml of deionized water and ultrasonicated for 20 min to completely disperse it, and 25 ml of an electrolyte containing 2 mol / L zinc sulfate was prepared, named DES0.
[0041] Using zinc foil as positive and negative electrodes and glass fiber as separator, 120 μL of the above electrolyte was taken to assemble a CR2032 button-type symmetrical battery, and the cyclic charge and discharge test was carried out on the Xinwei battery test system. The test temperature was 50°C and the current density was 0.25 mA cm -2 , the surface capacity is 0.25 mAh cm -2 .
[0042] The test results are as follows Figure 2 As shown, the symmetrical battery assembled by Comparative Example 2 can only be cycled for about 50 hours at 50°C due to the increase in temperature, the side reactions such as zinc dendrites and hydrogen evolution corrosion in the cycle are aggravated, and the cycle life of the battery is greatly shortened. In contrast, the Zn-Zn battery assembled by the zinc-based eutectic electrolyte selected in Example 2 can be cycled for about 200 hours, indicating that the zinc-based hydrated deep eutectic electrolyte prepared by the present invention has good applicability under high temperature conditions.
[0043] Example 3
[0044] A hydrated deep eutectic electrolyte for all-weather zinc-based batteries, levulinic acid and deionized water are mixed at a volume ratio of 1:1 and stirred at room temperature as a solvent, then zinc sulfate is added as a solute to control its concentration to 2 mol / L, and stirred at room temperature for 60 minutes to obtain a clear and transparent electrolyte named DES50. The above hydrated deep eutectic electrolyte is used to verify the effect of levulinic acid on inducing uniform deposition of zinc ions.
[0045] Using zinc foil as positive and negative electrodes and glass fiber as separator, 120 μL of the above electrolyte was taken to assemble a CR2032 button-type symmetrical battery, and the cyclic charge and discharge test was carried out on the Xinwei battery test system. The test temperature was 50°C and the current density was 0.25 mA cm -2 , the surface capacity is 0.25 mAh cm -2 .
[0046] Comparative Example 3
[0047] At room temperature, 14.378 g of zinc sulfate heptahydrate was added to 25 ml of deionized water and ultrasonicated for 20 min to completely disperse it, and 25 ml of an electrolyte containing 2 mol / L zinc sulfate was prepared, named DES0.
[0048] Using zinc foil as positive and negative electrodes and glass fiber as separator, 120 μL of the above electrolyte was taken to assemble a CR2032 button-type symmetrical battery, and the cyclic charge and discharge test was carried out on the Xinwei battery test system. The test temperature was -20°C and the current density was 0.25 mA cm -2 , the surface capacity is 0.25 mAh cm -2 .
[0049] The test results are as follows Figure 2 As shown, the symmetrical battery assembled by Comparative Example 2, due to the temperature drop at -20°C, the ion transmission process of the symmetrical battery of Comparative Example 3 is hindered, the impedance increases, and it can only cycle for about 120 hours. In contrast, the Zn-Zn battery assembled by the zinc-based eutectic electrolyte selected in Example 3 can stably cycle for about 720 hours, showing good electrochemical performance, which shows that the zinc-based hydrated deep eutectic electrolyte prepared by the present invention has good applicability under low temperature conditions.
[0050] Example 4
[0051] An all-weather zinc-based battery hydrated deep eutectic electrolyte, levulinic acid and deionized water are mixed at a volume ratio of 1:1 and stirred at room temperature as a solvent, then the solute zinc sulfate is added to control its concentration to 2 mol / L, and stirred at room temperature for 60 minutes to obtain a clear and transparent electrolyte named DES50. The above zinc-based hydrated deep eutectic electrolyte is used to verify the effect of levulinic acid on inhibiting the occurrence of side reactions.
[0052] Using zinc foil as positive and negative electrodes and glass fiber as separator, 120 μL of the above electrolyte was taken to assemble a CR2032 button-type symmetrical battery, and the cyclic charge and discharge test was carried out on the Xinwei battery test system. The test temperature was 25°C and the current density was 5 mA cm -2 , with a surface capacity of 1 mAh cm -2 .
[0053] Figure 4 The X-ray diffraction characterization of zinc deposition shows that all characteristic peaks match well with the standard phase of metallic zinc (PDF#78-0246), and the Zn(101) peak intensity is the highest, indicating that in this embodiment, the main crystal plane of zinc ion deposition is the Zn(101) crystal plane perpendicular to the basal plane, and very little byproduct Zn4SO4OH6·5(H2O) is observed. This result shows that the hydrated deep eutectic electrolyte prepared by the present invention can greatly inhibit the occurrence of side reactions.
[0054] Comparative Example 4
[0055] At room temperature, 14.378 g of zinc sulfate heptahydrate was added to 25 ml of deionized water and ultrasonicated for 20 min to completely disperse it, and 25 ml of an electrolyte containing 2 mol / L zinc sulfate was prepared, named DES0.
[0056] Using zinc foil as positive and negative electrodes and glass fiber as separator, 120 μL of the above electrolyte was taken to assemble a CR2032 button-type symmetrical battery, and the cyclic charge and discharge test was carried out on the Xinwei battery test system. The test temperature was 25°C, the current density was 5 mA·cm-2, and the surface capacity was 1 mAh·cm -2 .
[0057] Figure 4 X-ray diffraction characterization of zinc deposition shows that all characteristic peaks match well with the standard phase of metallic zinc (PDF#78-0246), and the Zn(101) peak intensity is the highest, indicating that in this embodiment, the main crystal plane of zinc ion deposition is the Zn(101) crystal plane perpendicular to the basal plane, and the formation of a large amount of by-product Zn4SO4OH6·5(H2O) is observed.
[0058] Example 5
[0059] An all-weather zinc-based battery hydrated deep eutectic electrolyte, levulinic acid and deionized water are mixed at a volume ratio of 1:1 and stirred at room temperature as a solvent, then the solute zinc sulfate is added to control its concentration to 2 mol / L, and stirred at room temperature for 60 minutes to obtain a clear and transparent electrolyte named DES50. The above zinc-based hydrated deep eutectic electrolyte is used to verify the effect of levulinic acid on inhibiting the occurrence of side reactions.
[0060] Using zinc foil as positive and negative electrodes and glass fiber as separator, 120 μL of the above electrolyte was taken to assemble a CR2032 button-type symmetrical battery, and the cyclic charge and discharge test was carried out on the Xinwei battery test system. The test temperature was 25°C and the current density was 5 mA cm -2 , with a surface capacity of 1 mAh cm -2 .
[0061] Figure 5 a is the scanning electron microscope characterization of zinc deposition in Example 5. It can be seen that due to the directional induction of levulinic acid, zinc ions are deposited in a layered stacking morphology parallel to the basal plane without obvious dendrites. And the formation of very little byproduct Zn4SO4OH6·5(H2O) is observed. This result shows that the hydrated deep eutectic electrolyte prepared by the present invention can greatly inhibit the occurrence of side reactions.
[0062] Comparative Example 5
[0063] At room temperature, 14.378 g of zinc sulfate heptahydrate was added to 25 ml of deionized water and ultrasonicated for 20 min to completely disperse it, and 25 ml of an electrolyte containing 2 mol / L zinc sulfate was prepared, named DES0.
[0064] Using zinc foil as positive and negative electrodes and glass fiber as separator, 120 μL of the above electrolyte was taken to assemble a CR2032 button-type symmetrical battery, and the cyclic charge and discharge test was carried out on the Xinwei battery test system. The test temperature was 25°C and the current density was 5 mA cm -2 , with a surface capacity of 1 mAh cm -2 .
[0065] Figure 5 b is the scanning electron microscope characterization of the zinc deposition in Example 5. It can be seen that the zinc deposition in Comparative Example 5 has a loose structure, with many disordered dendrites and irregular hexagonal deposits, which may aggravate the corrosion reaction and the accumulation of by-products, ultimately leading to battery failure, and the formation of a large amount of by-product Zn4SO4OH6·5(H2O) was observed.
[0066] Example 6
[0067] A hydrated deep eutectic electrolyte for all-weather zinc-based batteries, levulinic acid and deionized water are mixed at a volume ratio of 1:1 and stirred at room temperature as a solvent, then zinc sulfate is added as a solute to control its concentration to 2 mol / L, and stirred at room temperature for 60 minutes to obtain a clear and transparent electrolyte named DES50. The above hydrated deep eutectic electrolyte is used to verify the effect of levulinic acid on the capacity decay of the whole battery.
[0068] VOX positive electrode preparation process: Dissolve vanadium oxide (V2O5, Macklin, 99%, 0.3g) in 10mL 2M sodium chloride (NaCl) aqueous solution, stir continuously for 72h, and wash the formed orange-red gel several times with deionized water and ethanol. Then dry it in a vacuum oven at 80°C for 12 hours, take it out after cooling, filter the solution, dry it, grind it for use. Take 80mg of the above-prepared V2O5, mix it with SuperP and polyvinylidene fluoride in a mass ratio of 7:2:1, grind it in an agate mortar for 30min, add N-methylpyrrolidone, stir for 12h, and then use a scraper to evenly apply it on the surface of the titanium foil. After it is completely dried, slice it for use.
[0069] The VOX cathode material prepared above was used as the cathode, zinc foil as the anode, and glass fiber as the separator. 120 μL of the electrolyte was taken to assemble a CR2032 aqueous zinc ion button-type full battery, and the cycle charge and discharge test was carried out in the Xinwei battery test system. The current density was 1A·g -1 .
[0070] Comparative Example 6
[0071] At room temperature, 14.378 g of zinc sulfate heptahydrate was added to 25 ml of deionized water and ultrasonicated for 20 min to completely disperse it, and 25 ml of electrolyte containing 2 mol / L zinc sulfate was prepared, named DES0. The VOX positive electrode material prepared in the same way as in Example 6 was used, and zinc foil was used as the negative electrode and glass fiber was used as the separator to assemble a CR2032 type aqueous zinc ion button-type full battery for cyclic charge and discharge testing in the Xinwei battery test system. The current density was 1 A·g -1 .
[0072] The test results are as follows Figure 6 As shown, Example 6 uses zinc flakes (100 μm) at 1 A·g -1 The discharge capacity under the conditions of , can maintain 70.5% after 1000 cycles, and the discharge capacity of comparative example 6 decays to 35.5% after about 1000 cycles. This result shows that the hydrated deep eutectic electrolyte prepared by the present invention can reduce the occurrence of various side reactions, maintain good electrochemical cycle performance, reduce capacity loss, and improve the reversibility of zinc deposition / stripping reaction.
[0073] Compared with the prior art, the all-weather zinc-based hydrated deep eutectic electrolyte provided by the present invention, zinc salts and hydrogen-bonding ligands are mixed to form a eutectic solvent, which is in a liquid state at room temperature. Through the action of hydrogen bonds, the solubility of zinc salts and hydrogen-bonding ligands is improved, thereby improving the conductivity of the battery and the stability of the electrolyte. Importantly, the electrolyte of the present invention exhibits a high charge and discharge capacity and excellent cycle stability under all-weather conditions (-20°C to 50°C), effectively expands the operating temperature range of aqueous zinc-ion batteries, solves the problems of zinc negative electrode side reactions and dendrite growth at high and low temperatures, greatly prolongs the service life of aqueous zinc-ion batteries, and is of great significance in the field of energy storage. In addition, the preparation method of the all-weather zinc-based hydrated deep eutectic electrolyte provided by the present invention is simple, fast, low-cost, safe, green and pollution-free, and suitable for large-scale promotion and application.
[0074] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A hydrated deep eutectic electrolyte for all-weather zinc-based batteries, characterized in that: The electrolyte consists of a zinc salt, a hydrogen bonding ligand and additional water solvent.
2. The all-weather zinc-based battery hydrated deep eutectic electrolyte according to claim 1, characterized in that: The volume ratio of the water solvent to the hydrogen bonding ligand is 1:1-5, and the concentration of the zinc salt aqueous solution in the electrolyte is maintained at 2 mol·L -1 .
3. The all-weather zinc-based battery hydrated deep eutectic electrolyte according to claim 1, characterized in that: The zinc salt includes at least one of Zn(ClO4)2·6H2O, Zn(BF4)2·6H2O and ZnSO4·7H2O.
4. The all-weather zinc-based battery hydrated deep eutectic electrolyte according to claim 1, characterized in that: The hydrogen bonding ligand includes at least one of acetylacetone, acetylacetone and acetylacetic acid.
5. The all-weather zinc-based battery hydrated deep eutectic electrolyte according to claims 1 to 4, characterized in that: Used in the preparation of all-weather zinc-based batteries.
6. An all-weather aqueous zinc-based battery, characterized in that: It comprises a positive electrode, a negative electrode and the all-weather zinc-based battery hydrated deep eutectic electrolyte as described in claims 1 to 4, wherein the preparation method of the positive electrode is to load at least one of a conductive polymer and a vanadium-based compound on a substrate.
7. The all-weather aqueous zinc ion battery according to claim 6, characterized in that: The conductive polymer is at least one of polyaniline and polypyrrole; the vanadium-based compound is at least one of vanadium dioxide, vanadium pentoxide, sodium vanadate, basic zinc vanadate, sodium vanadium phosphate and sodium vanadium parafluorophosphate; the substrate is commercial carbon paper and titanium foil roughened by acid etching; the loading amount of at least one of the conductive polymer and the vanadium-based compound on the substrate is 2 to 20 mg cm -2 The electrode thickness is between 0.15 and 1.5 mm, and the tap density is between 0.6 and 3.5 g / cm 3 .
8. The all-weather aqueous zinc-based battery according to claim 6, characterized in that: The loading method includes in-situ polymerization, scraping film formation or hydrothermal synthesis; the negative electrode is a high-purity zinc metal foil with a thickness of 10 to 100 μm, or is obtained by anode deposition of zinc film or brushing of zinc slurry on titanium foil, stainless steel foil or carbon paper, and the thickness is controlled to be 5 to 30 μm.
9. The method for preparing an all-weather aqueous zinc-based battery according to any one of claims 6 to 8, characterized in that: The method comprises the following steps: assembling the positive electrode, the hydrated deep eutectic electrolyte according to any one of claims 1 to 4 and the negative electrode into aqueous zinc ion batteries with different device structures.
10. The method for preparing an all-weather aqueous zinc-based battery according to claim 9, characterized in that: The method specifically uses glass fiber as a separator. If a standard button shell is used to encapsulate a button battery at a pressure of 70-90 MPa, the amount of hydrated deep eutectic electrolyte added is 50-100 μL.
Citation Information
Patent Citations
Deep eutectic solvent, preparation method thereof, and application of solvent as extractant
CN110128235A
Aqueous, alkaline electrolyte for depositing zinc-containing layers onto surfaces of metal piece goods
CN110291229A
Hydrated deep eutectic electrolyte and application thereof in wide-temperature-range zinc ion battery
CN118367242A
Nonaqueous electrolyte secondary battery
JP2006172726A